(untitled) (Research, Society and Development, 2022)
Objective: To map the body patterns exposed by social media that influence the construction of adolescents’ body image. Method: This protocol was developed according to the recommendations of the Joanna Briggs Institute Manual and was registered in the Open Science Framework. The search for articles will be carried out in the PubMed, Web of Science, ScienceDirect, Medline, lilacs and SciELO databases, as well as additional sources from the gray literature and list of references of the included studies. The terms “adolescent”, “body image”, “Social media”, “YouTube”, “Instagram”, “Facebook”, “TikTok”, “Twitter Messaging”, “WhatsApp”, “Snapchat”, “social networking website” and related words will be used in the search strategy. Editorials, review articles and letters to the editor will be excluded; and experimental and quasi-experimental studies will be included; also, descriptive and analytical observational, qualitative and quantitative approach. The study selection period will be from September 1 to September 30, 2022. The Rayyan software will be used for export the freely selected studies. The selection and extraction of data from the studies included in the review will be carried out independently by two reviewers, through a form developed by the authors themselves, following the suggestion of the JBI Manual. In cases of divergences, it will be resolved by a third reviewer. The data will be extracted through a form and presented in a chart and/or images and in a descriptive way. This protocol will assist in the development of the scope review for the identification of gaps and synthesis of knowledge for the conduct of future studies.